1986
DOI: 10.1111/j.1445-2197.1986.tb07099.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Outcomes of Neurotrauma in New South Wales

Abstract: This study of 1161 neurotrauma patients in New South Wales hospitals was designed to examine the role of preventable causes of death and disability in cases of spinal injury, extradural, subdural and multiple intracranial haematomas in order to make recommendations for improvements in accident, emergency, ambulance and hospital services. Methods have been developed for standardizing diagnosis in different classes of hospital for the assessment of severity in terms of the patient's age, sex, physical signs, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In 1976, Jennett presented two cases series from Glasgow and the Netherlands of outcomes of patients hospitalised with severe head injury and evidence of at least six hours of coma. The results of these studies are similar to those described by Ring et al (1986) in _ Australia (Jennett 1976).…”
Section: Rest Of the Worldsupporting
confidence: 90%
See 1 more Smart Citation
“…In 1976, Jennett presented two cases series from Glasgow and the Netherlands of outcomes of patients hospitalised with severe head injury and evidence of at least six hours of coma. The results of these studies are similar to those described by Ring et al (1986) in _ Australia (Jennett 1976).…”
Section: Rest Of the Worldsupporting
confidence: 90%
“…Neurotrauma and its outcomes, however, are well researched (Ford 1976;Simpson et al 1984;Burke et al 1985;Jones et al 1986, Cain et al 1989Ryan 1992) and it has been shown that neurotrauma was responsible for 70% of all road accident deaths and 50% of all deaths from external causes. About 51 % of neurotrauma patients died, 1 % survived in vegetative states, 14% had severe disability 13% had moderate disability and 22% made a good recovery (Ring et al 1986).…”
Section: Australiamentioning
confidence: 99%
“…First, neurotrauma has been shown to be more common in rural areas than in urban areas per capita in a number of epidemiological studies from the Australian states. [2][3][4][5] Second, rural neurotrauma is associated with a higher mortality and morbidity than neurotrauma occurring in urban settings. 3,22 Although there have been significant improvements in all aspects of rural neurotrauma management in Australia in the past 30 years, 23 there also continues to be significant deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of aspects to this challenge. First, neurotrauma has been shown to be more common in rural areas than in urban areas per capita in a number of epidemiological studies from the Australian states 2–5 . Second, rural neurotrauma is associated with a higher mortality and morbidity than neurotrauma occurring in urban settings 3,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation